Electrical Resistivity of Fe‐C Alloy at High Pressure: Effects of Carbon as a Light Element on the Thermal Conductivity of the Earth's Core. Issue 5 (19th May 2018) - Zhang, Chengwei; Lin, Jung‐Fu; Liu, Ying; Feng, Shaomin; Jin, Changqing; Hou, Mingqiang; Yoshino, Takashi
Abstract: We measured the electrical resistivity of iron, Fe99 C1, Fe3 C, and Fe7 C3 up to ~80 GPa using the van der Pauw method in a diamond anvil cell. The electrical resistivity of disordered Fe99 C1 at high pressure shows a strong impurity resistivity of carbon. The ferromagnetic‐paramagnetic transition in Fe3 C and Fe7 C3 is associated with the flattening of the resistivity pressure gradient at ~6 GPa. Fe7 C3 exhibits the highest electrical resistivity among all iron‐light element alloys, and Fe3 C and Fe7 C3 disobey the Matthiessen's rule by showing a lower electrical resistivity than a disordered iron‐carbon alloy because of chemical ordering. A comparison of the impurity resistivity between silicon, sulfur, nickel, and carbon shows that carbon has an exceedingly stronger alloying effect than other elements. If the chemical ordering observed in Fe‐Si system is held true for the Fe‐C system, the chemical ordering in Fe7 C3 possibly increases the thermal conductivity of the inner core and enlarges the thermal and electrical conductivity gap at the inner‐core boundary. Models of the thermal conductivity of liquid Fe70 C30 with 8.4 wt % carbon show a low thermal conductivity of 38 Wm −1  K −1 at the pressure‐temperature conditions of the topmost outer core. The corresponding heat flow of 6 TW at the core‐mantle boundary is notably lower than previous electrical resistivity results on Fe and Fe alloys. The alloying effect of carbon on the electrical and thermal conductivity of iron can thus play a significant role in understanding the heat flux at the core‐mantle boundary and the thermal evolution of the core. Key Points: The electrical resistivity of pure iron, Fe99 C1, and iron carbides (Fe3 C and Fe7 C3 ) was measured at pressures up to 80 GPa Carbon has a stronger alloying effect in reducing the electrical and thermal conductivities in the Earth's core than that of Si, S, and Ni Earth's core in an Fe‐C composition will have a low heat flow at the core‐mantle boundary and a conductivity gap at the inner‐core boundary